2014
DOI: 10.1002/bjs.9355
|View full text |Cite
|
Sign up to set email alerts
|

MRI-defined height of rectal tumours

Abstract: There was up to 5.5 cm variation, depending on which landmark was chosen for reporting the distal margin of rectal cancer. This has potential implications for surgical planning, interpreting radiological images and comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…A potential criticism of this study would be the use of MRI instead of proctoscopy to measure distance from the anal verge. However, a previous study has described the difference in heights on MRI and proctoscopy as less than 1 cm . We did not corroborate our MRI lengths with proctoscopy, although previous in vivo studies on metric measurements using rigid endoscopy have confirmed a wide variation in rectal length .…”
Section: Discussioncontrasting
confidence: 92%
“…A potential criticism of this study would be the use of MRI instead of proctoscopy to measure distance from the anal verge. However, a previous study has described the difference in heights on MRI and proctoscopy as less than 1 cm . We did not corroborate our MRI lengths with proctoscopy, although previous in vivo studies on metric measurements using rigid endoscopy have confirmed a wide variation in rectal length .…”
Section: Discussioncontrasting
confidence: 92%
“…Eligible patients were those presenting with a tumour 15 cm or less from the anal verge measured by MRI. Patients who underwent low anterior resection for primary adenocarcinoma of the rectum with curative intent were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluated cases, all data were collected anonymously with entry as case numbers. In order to calculate the distance from the anal verge (AV) when only distance from anorectal junction was provided, the tumor distance measured from the anorectal junction was corrected by adding four centimeters for males and females [14][15][16][17]. The part of the rectum in which the tumor was situated was defined by distance from the AV as 0-6 cm, 7-11 cm, and 12-15 cm for low, mid, and high rectum, respectively [15].…”
Section: Patientsmentioning
confidence: 99%